2019
DOI: 10.1002/ppsc.201800517
|View full text |Cite
|
Sign up to set email alerts
|

DTT–Au NCs Interact with DNA to Form Raspberry‐Like Particles

Abstract: Noble metal nanoclusters (NCs) have emerged as intriguing nanomaterials with widespread interest. Previously, it was shown that dithiothreitol (DTT)‐conjugated gold nanoclusters (Au NCs) respond to copper ions in aqueous solution. Here, it is shown that these DTT–Au NCs can interact with DNA by forming raspberry‐like particles. The raspberry‐like structures protect the capped DNA from enzymatic attack and show excellent biocompatibility. Moreover, these supramolecular complexes cross the plasma membrane of yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Li et al used the hybrids doped by tryptophan to load the plasmids expressing green fluorescent protein into the cells and expressed the green fluorescent protein in the yeast cells 100 . Zhang et al used the DTT protected gold nanoclusters to load the plasmids expressing green fluorescent protein into the cells and expressed the green fluorescent protein in the yeast cells 101 . It also opened up a new way for gene therapy by using protein Au NCs instead of viruses.…”
Section: Study On the Application Of Protein Au Ncsmentioning
confidence: 99%
“…Li et al used the hybrids doped by tryptophan to load the plasmids expressing green fluorescent protein into the cells and expressed the green fluorescent protein in the yeast cells 100 . Zhang et al used the DTT protected gold nanoclusters to load the plasmids expressing green fluorescent protein into the cells and expressed the green fluorescent protein in the yeast cells 101 . It also opened up a new way for gene therapy by using protein Au NCs instead of viruses.…”
Section: Study On the Application Of Protein Au Ncsmentioning
confidence: 99%
“…Nucleic acids represent another big class of biomolecules which are extensively exploited in the field of nanobiomaterials. Nanotechnologies based on DNA strands have become highly demanding, as they can provide high-level tasks such as gene therapy and DNA-target-recognition techniques [ 107 , 108 ]. Recently, DNA was also tested as a promising ligand for AuNCs.…”
Section: Design and Application Of Auncs For Bioimagingmentioning
confidence: 99%
“…In particular, this constituted a promising sensor-free diagnostic platform for the detection of cancer. Chen and co-workers showed that the interaction of DNA with dithiothreitol (DTT)-conjugated gold nanoclusters (Au NCs) results in the formation of 'raspberry-like' particles with potential gene delivery application [99]. The novelty of the 'raspberry-like' structures lay in their biocompatible 'shield', which protected the capped DNA from enzymatic degradation.…”
Section: Dna-metal Nanoparticle Architecturesmentioning
confidence: 99%